The Impact of Engoo Web Application on Students’ Reading Ability: A Quasi-Experimental Study - Gumawang, Bintang Ilham; Dewi, Puspa; Johan, Andrian Nuriza (Jurnal Pendidikan Bahasa Inggris Proficiency, 2026)
This study aimed to test the effectiveness of the Engoo Web App in improving fifth-grade students' English reading skills. A quantitative experimental research design was used involving 60 students, divided into an experimental group and a control group. Data were collected using pre-test and post-test instruments and analyzed through descriptive statistics, N-Gain analysis, and the Mann–Whitney U test. The results showed that the experimental group achieved a higher mean post-test score (M = 82.45) than the control group (M = 71.30), with a moderate N-Gain of 0.56, compared to 0.28 in the control group. The Mann–Whitney U test revealed a statistically significant difference between the two groups (p < 0.05), indicating that the improvement in reading skills was influenced by the instructional treatment. The effectiveness of the Engoo Web App can be attributed to its interactive and multimodal features, including structured reading materials, pronunciation guides, and audio support, which align with constructivist learning principles and encourage active student engagement. Despite its positive findings, this study is limited by its small sample size and short intervention period. Future research is recommended to involve larger samples and longer treatment durations to further explore the long-term effects of digital reading platforms on the development of English reading skills.